Which Support Pants are the Most Effective for Burning Body Fat? (Journal of Fiber Bioengineering and Informatics, 2016)
Obesity is the main cause of lifestyle-related disease, which is in turn the main cause of death in Japan.Aerobic exercise is more effective than anaerobic exercise in burning body fat. The present studyidentified conditions that enhance the burning of body fat during aerobic exercise, including the effectsof wearing support pants. Twenty-one young Japanese women completed aerobic exercise sessions whilewearing each of three types of support pants. Total body fat burning during aerobic exercise was 16times greater than that at rest. Partial-compression garments helped reduce body fat more efficientlythan both non-compression and constant-compression pants.
Keywords: Support Pants; Body Fat Burning; Aerobic Exercise; Respiratory Metabolism; Clothing Pressure